An evolutionary medicine perspective on Neandertal extinction. Issue 108 (July 2017) - Sullivan, Alexis P.; de Manuel, Marc; Marques-Bonet, Tomas; Perry, George H.
Abstract: The Eurasian sympatry of Neandertals and anatomically modern humans – beginning at least 45, 000 years ago and possibly lasting for more than 5000 years – has sparked immense anthropological interest into the factors that potentially contributed to Neandertal extinction. Among many different hypotheses, the "differential pathogen resistance" extinction model posits that Neandertals were disproportionately affected by exposure to novel infectious diseases that were transmitted during the period of spatiotemporal sympatry with modern humans. Comparisons of new archaic hominin paleogenome sequences with modern human genomes have confirmed a history of genetic admixture – and thus direct contact – between humans and Neandertals. Analyses of these data have also shown that Neandertal nuclear genome genetic diversity was likely considerably lower than that of the Eurasian anatomically modern humans with whom they came into contact, perhaps leaving Neandertal innate immune systems relatively more susceptible to novel pathogens. In this study, we compared levels of genetic diversity in genes for which genetic variation is hypothesized to benefit pathogen defense among Neandertals and African, European, and Asian modern humans, using available exome sequencing data (three individuals, or six chromosomes, per population). We observed that Neandertals had only 31–39% as many nonsynonymous (amino acid changing) polymorphisms across 73 innate immune system genes compared to modern human populations. We also found that Neandertal genetic diversity was relatively low in an unbiased set of balancing selection candidate genes for primates, those genes with the highest 1% genetic diversity genome-wide in non-human hominoids (apes). In contrast, Neandertals had similar or higher levels of genetic diversity than humans in 12 major histocompatibility complex ( MHC ) genes. Thus, while Neandertals may have been relatively more susceptible to some novel pathogens and differential pathogen resistance could be considered as one potential contributing factor in their extinction, the expectations of this model are not universally met.